2021
DOI: 10.1128/jvi.00154-21
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topology of Pestiviral Nonstructural Protein 2 and Determination of the Minimal Autoprotease Domain

Abstract: Pestiviruses like bovine viral diarrhea virus (BVDV) belong to the family Flaviviridae. A distinctive feature of the Flaviviridae is the importance of non-structural (NS) proteins for RNA genome replication and virus morphogenesis. For pestiviruses, the NS2 protease-mediated release of NS3 is essential for RNA replication, whereas uncleaved NS2-3 is indispensable for producing viral progeny. Accordingly, in the pestiviral life cycle the switch from RNA replication to virion morphogenesis is temporally regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 63 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…In summary, we demonstrated that internal cleavage in NS2 is mediated by the NS3/4A protease and occurs between L188 and G189, separating NS2 into two parts: (1) a membrane-bound, N-terminal fragment containing the complete NS2 transmembrane domain, and (2) a soluble, C-terminal part containing the NS2 protease active site (). For the latter part, we do not expect any NS2 cysteine protease activity according to the data of Walther et al [21], resulting in a large cleavage product consisting of the NS2 C-terminal domain (NS2 C-ter .) followed by NS3.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…In summary, we demonstrated that internal cleavage in NS2 is mediated by the NS3/4A protease and occurs between L188 and G189, separating NS2 into two parts: (1) a membrane-bound, N-terminal fragment containing the complete NS2 transmembrane domain, and (2) a soluble, C-terminal part containing the NS2 protease active site (). For the latter part, we do not expect any NS2 cysteine protease activity according to the data of Walther et al [21], resulting in a large cleavage product consisting of the NS2 C-terminal domain (NS2 C-ter .) followed by NS3.…”
Section: Resultsmentioning
confidence: 75%
“…Immunoprecipitation of N-terminally H-F-tagged BVDV NS2 indicates internal NS2 processing. ( a ) Schemes of BVDV-1 NCP7- and CP7-derived expression constructs pTM7 NCP7 and CP7 p7-4A 2/H-F, respectively, encoding the p7 to NS4A region with N-terminally HA-Flag ( H- F)-tagged NS2 as described previously [21]. The BVDV-1 strain CP7-specific nine aa insertion in NS2 is displayed in a red box [25]; the H-F epitopes are indicated in green.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations